1996
DOI: 10.1006/dbio.1996.0208
|View full text |Cite
|
Sign up to set email alerts
|

Early Embryonic Lethality Caused by Targeted Disruption of the Mouse Thioredoxin Gene

Abstract: Thioredoxins belong to a widely distributed group of small proteins with strong reducing activities mediated by a consensus redox-active dithiol (Cys-Gly-Pro-Cys). Thioredoxin was first isolated as a hydrogen donor for enzymatic synthesis of deoxyribonucleotides by ribonucleotide reductase in Escherichia coli. Recent studies have revealed a variety of roles that thioredoxin plays in transcription, growth control, and immune function. In this report, we describe the phenotype of mice carrying a targeted disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
292
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(305 citation statements)
references
References 0 publications
6
292
0
4
Order By: Relevance
“…This study set out to further our understanding of the in vivo functions of Grx1 using a line of knockout mice deficient in this enzyme. In contrast to mice deficient in Trx1 or Trx2, which die in utero [57,58], mice lacking Grx1 develop normally and are healthy upon observation to one year of age, indicating the distinct functions of Trxs and Grx1 in mouse development.…”
Section: Discussionmentioning
confidence: 91%
“…This study set out to further our understanding of the in vivo functions of Grx1 using a line of knockout mice deficient in this enzyme. In contrast to mice deficient in Trx1 or Trx2, which die in utero [57,58], mice lacking Grx1 develop normally and are healthy upon observation to one year of age, indicating the distinct functions of Trxs and Grx1 in mouse development.…”
Section: Discussionmentioning
confidence: 91%
“…Two Trxs have been identified in humans, one cytosolic (hTrx1) [1] and one mitochondrial (hTrx2) [2]. Knockout mice null for either Trx1 or Trx2 are embryonically lethal [16,17], which demonstrates the essential roles of Trx1 and Trx2 in mammals. Trx1 plays an important role in maintaining the reduced environment in cells through thiol-disulfide exchange reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the physiologically important roles of Trx include: 1) acting as a hydrogen donor for enzymes involved in reductive reactions [38]; 2) maintaining a reduced environment in cells [9]; 3) controlling protein (especially transcription factors) function via the redox state [1012] and the expression of target genes; 4) protecting cells and tissues from oxidative stress [13]; and 5) having anti-apoptotic effects through the inhibition of the ASK [14] and mitochondrial pathways [15]. The essential biological roles of Trx were further supported by two studies which demonstrated that mice null for either Trx1 or Trx2 were embryonically lethal [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the TRX protein may contribute to the regulation or the modulation of oxidative stress in embryos. In this regard, it is interesting to note that homozygous mutant mouse embryos that lack the Trx gene die shortly after implantation [41], which corresponds to the stage when the TRX protein expression begins in WT embryos. These previous findings suggest that the protective effects of TRX against teratogenesis of early mouse embryos that we observed in the present study may be due to TRX-mediated attenuation of the embryopathic effects of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%